The Influence of Coordination on Employe Work Effectiveness in the General and Personnel Subdivision of the Fisheries Office of West Seram Regency - Raynaldo Corputty; Petronela Sahetapy; Hengky Virgo Richardo Pattimukay (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
This study aims to analyze the effect of coordination on employee work effectiveness in the General and Staffing Subdivision of the Fisheries Office of West Seram Regency. The organizational issues identified in this study relate to the suboptimal achievement of work targets, which are suspected to be influenced by inadequate coordination among personnel and units. This research employs a quantitative approach, using a survey method and distributing questionnaires to employees as respondents. The validity and reliability tests show that all items in the coordination variable (X) and employee work effectiveness variable (Y) are valid and reliable (αX = 0.904; αY = 0.887). The classical assumption tests—including normality, multicollinearity, autocorrelation, and heteroscedasticity—indicate that the data meet all regression model requirements. The simple linear regression analysis yields the equation Y = 15.432 + 0.684X, indicating that coordination positively influences employee work effectiveness. The F-test reveals that the model is significant (F = 49.873; Sig. = 0.000), while the t-test shows that the coordination variable significantly affects employee effectiveness (t = 7.062; Sig. = 0.000). Thus, the research hypothesis is accepted. These findings reinforce modern management theories and the perspectives of scholars such as Fayol, Terry, and Robbins, who emphasize coordination as a critical element in achieving organizational effectiveness. The results also align with Fitria's (2021) findings, which state that coordination and communication are key determinants of employee effectiveness in public service organizations. Overall, this study concludes that improved coordination—through communication, briefings, meetings, and harmonious work relationships—significantly enhances the work effectiveness of employees in the General and Staffing Subdivision of the Fisheries Office of West Seram Regency.